Design of 24/7 continuous hydrogen production system employing the solar-powered thermochemical S–I cycle. (21st September 2020) - Cumpston, Jeff; Herding, Robert; Lechtenberg, Fabian; Offermanns, Christoph; Thebelt, Alexander; Roh, Kosan
Abstract: We propose a system design for continuous and emission-free hydrogen production using the thermochemical Sulfur–Iodine cycle. Process heat required for the sulfuric acid decomposition is exclusively generated by a combination of concentrating solar thermal parabolic trough and solar tower systems, which are operated during the daytime only. The proposed design relies on the decoupling of the high temperature section from the rest of the process through material and energy storage for continuous operation. We conceptually design the whole process via steady-state simulation and assess its thermal efficiency and economics. We reveal that the proposed system is comparable to its alternatives in terms of the heat-to-hydrogen efficiency (38.0%) and the levelized cost of hydrogen 10.4 $/kg H 2 . Since the levelized cost is primarily attributed to the capital investment, enlarging the proposed system will lead to significant cost reduction due to economies-of-scale. Highlights: Continuous hydrogen production system based on Sulfur–Iodine cycle is proposed. The whole system is powered by solar thermal energy. Material and energy storage systems enable continuous operation. Conceptual process design is conducted to assess process performances. Thermal efficiency & levelized cost of hydrogen are comparable to the alternatives.